2009
DOI: 10.1158/1055-9965.epi-08-0832
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Role of Cytochrome P450 2E1 and Glutathione-S-Transferase Activity for Acrylamide Toxicokinetics in Humans

Abstract: Acrylamide, a potential food carcinogen in humans, is biotransformed to the epoxide glycidamide in vivo. Both acrylamide and glycidamide are conjugated with glutathione, possibly via glutathione-S-transferases (GST), and bind covalently to proteins and nucleic acids. We investigated acrylamide toxicokinetics in 16 healthy volunteers in a four-period change-over trial and evaluated the respective role of cytochrome P450 2E1 (CYP2E1) and GSTs. Participants ingested selfprepared potato chips containing acrylamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 63 publications
3
37
0
1
Order By: Relevance
“…The use of disulfiram in studies aimed to inactivate CYP2E1 in vivo has been reported recently (Doroshyenko et al, 2009); however, the mechanism by which it causes inactivation has not been reported. We report here that disulfiram is not the compound directly responsible for inactivation of CYP2E1, but that its reduced form, diethyldithiocarbamate, is responsible for the inactivation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of disulfiram in studies aimed to inactivate CYP2E1 in vivo has been reported recently (Doroshyenko et al, 2009); however, the mechanism by which it causes inactivation has not been reported. We report here that disulfiram is not the compound directly responsible for inactivation of CYP2E1, but that its reduced form, diethyldithiocarbamate, is responsible for the inactivation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2E1 is involved in the metabolism of numerous low-molecular-weight xenobiotics including acetaminophen, benzene, and chlorzoxazone, as well as anesthetics such as halothane (Koop, 1992;Lieber, 1997). Disulfiram has been used for a long time as an inhibitor of CYP2E1 in various in vivo studies (Doroshyenko et al, 2009). It has also been proposed that inhibition by disulfiram could be used to prevent the activation of nitrosamine carcinogens by CYP2E1 (Wattenberg et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded from the excretion kinetics that the exposure to acrolein is attributable to the intake of the test meal. The deep-frozen urine samples examined during these analyses originated from a study conducted earlier [97,98]. Test subjects consumed self-made potato chips with relatively high acrylamide content (acrylamide dose 1 mg).…”
Section: High Acrolein Contents In Fried Potatoes?mentioning
confidence: 99%
“…Glycidamide is mutagenic, and it is able to bind to DNA and cause genetic damage (Adler et al 2000;Yousef and El-Demerdash 2006). Glycidamide is subsequently metabolized through either GSH conjugation by GST or hydrolysis by epoxide hydrolase (Paulsson et al 2005;Doroshyenko et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…CYP2E1 is the classical alcohol-inducible CYP isoform which catalyzes several pro-carcinogens such as benzene, N-nitrosodimethylamine, styrene, into their carcinogenic forms. CYP2E1 is also a polymorphic enzyme (Ulusoy et al 2007a, b;Doroshyenko et al, 2009). While it was shown that acrylamide is metabolized primarily by liver CYP2E1, the effects of acrylamide on cytochrome-dependent drug metabolizing enzymes have not yet been characterized.…”
Section: Introductionmentioning
confidence: 99%